Development of Proprioceptive Acuity in Typically Developing Children: Normative Data on Forearm Position Sense - Holst-Wolf, Jessica M.; Yeh, I-Ling; Konczak, Jürgen (Frontiers in Human Neuroscience, 2016)
This study mapped the development of proprioception in healthy, typically developing children by objectively measuring forearm position sense acuity. We assessed position sense acuity in a cross-sectional sample of 308 children (5-17 y/o; M/F = 127/181) and a reference group of 26 healthy adults (18-25 y/o; M/F = 12/14) using a body-scalable bimanual manipulandum that allowed forearm flexion/extension in the horizontal plane. The non-dominant forearm was passively displaced to one of three target positions. Then participants actively matched the target limb position with their dominant forearm. Each of three positions was matched five times. Position error (PE), calculated as the mean difference between the angular positions of the matching and reference arms, measured position sense bias or systematic error. The respective standard deviation (SDPdiff) indicated position sense precision or random error. The main results are as follows: First, systematic error, measured as PE, did not change significantly from early childhood to late adolescence (Median PE at 90º target: -2.85º in early childhood; -2.28º in adolescence; 1.30º in adults). Second, response variability as measured by SDPdiff significantly decreased with age (Median SDPdiff at 90º target: 9.66º in early childhood; 5.30º in late adolescence; 3.97º in adults). The data of this large cross-sectional sample of children document that proprioceptive development in typically developing children is characterized as an age-related improvement in precision, not as a development or change in bias. In other words, it is the reliability of the perceptual response that improves between early childhood and adulthood. This study provides normative data against which position sense acuity in pediatric patient populations can be compared. The underlying neurophysiological processes that could explain the observed proprioceptive development include changes in the tuning of muscle spindles at the spinal level, the maturation of supraspinal somatosensory pathways, and the development of interhemispheric callosal connections responsible for the transfer of somatosensory information.